Financing Political Parties in Germany – the Case of Political Foundations - Paul, Sebastian; Vymětal, Petr; Ondráčka, David, 1976-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The thesis analyzes the current German political situation in terms of party financing. In particular, the special role that political foundations play in this connection and what influence they have on German political parties, decision makers and German politics in general, shall be examined. Political foundations are playing an important role in party financing and some of them are even operating internationally. Exactly what role they play is still not well known by the German public and many reports related to this topic do not exist. One of the main concerns of the thesis will consequently be on corruption and lobbying in the German political system.
Vedoucí práce: Petr Vymětal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses